(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
There was found to be a significant gap between theory on family business and performance measurement systems (PMSs): the theory underlines the importance of PMSs for family businesses, but little research on how implement these systems is available. In this study we propose the adoption of PMSs tools, specifically Balanced Scorecard (BSC), for family businesses; the design of the model depends on the typical issues of family businesses, more specifically social capital and trust, based on effective governance. Social capital represents a distinctive characteristic of family business. Considering that system trust constitutes the basis of social capital, we outline the role PMSs can play in sustaining system trust; PMSs are crucial to the alignment between the management and strategic vision of the organization.The BSC proposed represents a PMSstool that makes governance effective, because it creates the basis for alignment between management and strategic vision of the organization (both from family and business point of view), consistently with family members expectations. The study is organized in different sections. Firstly, we analyse the characteristic of family businesses that must be considered to design BSC: literature review includes the sources of sustainable competitive advantage, focusing the attention on the interaction between family and business, underlining the central role of social capital; then the concept of trust is investigated as it provides the basis of social capital. Secondly, we discuss how PMSs can be adopted to make governance effective. Then we consider the opportunity to adopt BSC as PMSs tool. On the basis of literature review, some propositions are presented to link family business, social capital, trust, PMSs and BSC. Finally, we propose a BSC model for family businesses: we also discuss the reasons why we have chosen BSC framework and the conditions under we have designed the model. Implications are drawn as conclusions; the paper ends with some limitations of the study and opportunities for further researches.